The Norton Scores : An Anthology for Listening - Edited by Kamien, Roger (New York W.W. Norton & Company, Inc., 1972)
"The Norton Scores is an anthology of music designed for the listener. In this revision, the one-volume Standard Edition includes forty-eight complete works and integral excerpts, ranging from a fifteenth-century motet by Josquin to twentieth century masterpieces by Schoenberg, Stravinksy, Bartók, Webern, and Copland, illustrating the major forms, genres, and composers. By the use of a unique highlighting system, the following of full orchestral scores is greatly facilitated for the novice score-reader, without obscuring any of the important subordinate lines and accompaniments. Rather than presenting "pre-digested" scores, The Norton Scores provides valuable experience in following the real thing...The Norton Scores is the most comprehensive and versatile anthology available for the varying needs of music students, whether they are beginners or more advanced, and the pedagogical soundness of the highlighting technique makes this book unique in its field."
Include Index
Keywords: Music appreciation -- Musical analysis